PENGEMBANGAN KOMPETENSI GURU PENDIDIKAN DASAR PASCA SERTIFIKASI - Nofrita, Dewi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
In order to achieve basic education goals, so the development of teachers and other educator are developed to improve the quality of education throughout the country. Education is improved and integrated cohesively in adequate amounts quality. Furthermore, the basic education of teachers is required to work regularly and consistently, but being creative in facing the job and stability in the works, should be personal characteristics. So, this pattern of this work’s type is inspired by learners by learners as education, since the stability and personal integration does not happen by itself, but growing through a process of education which is deliberately created.